IEEE Conference on Decision and Control and European Control Conference 2011
DOI: 10.1109/cdc.2011.6160633
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-initiative nested classification by optimal thresholding

Abstract: Abstract-The purpose of this paper is to demonstrate that having two classifiers, a trichotomous classifier (true, false, or unknown) with workload-independent performance that turns over the data classified as unknown to a binary classifier (true or false) with workload-dependent performance, gives superior classification performance (lower probability of misclassification) compared to a single dichotomous classifier. We relate the classifier's performance to the inherent difficulty of the classification task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This implies that if the workload-independent classifiers (machines) have better performances than the workloaddependent classifiers (human operators), there is no optimal solution for n. Similarly, it can be shown that for σ 1 < σ 2 , 2 Although we do not present a full proof for this claim due to page restriction, it can be easily shown with a similar argument presented in [2].…”
Section: A Analytical Propertiesmentioning
confidence: 76%
See 3 more Smart Citations
“…This implies that if the workload-independent classifiers (machines) have better performances than the workloaddependent classifiers (human operators), there is no optimal solution for n. Similarly, it can be shown that for σ 1 < σ 2 , 2 Although we do not present a full proof for this claim due to page restriction, it can be easily shown with a similar argument presented in [2].…”
Section: A Analytical Propertiesmentioning
confidence: 76%
“…In our previous work [2], [3], we considered a mixedinitiative nested classification where two heterogeneous classifiers are composed in a nested architecture. Figure 3 shows the concept.…”
Section: B Mixed-initiative Nested Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimal threshold is computed by minimizing the probability of misclassification (theory and examples of thresholding for classification can be found in [31]), The second order condition for a minimum is indeed satisfied:…”
Section: B Probability Of Misclassificationmentioning
confidence: 99%